2020
DOI: 10.3390/genes11090967
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Anomalies Associated with Novel Pathogenic Variants in TMEM94

Abstract: Background: Intellectual developmental disorder with cardiac defects and dysmorphic facies (IDDCDF, MIM 618316) is a newly described disorder. It is characterized by global developmental delay, intellectual disability and speech delay, congenital cardiac malformations, and dysmorphic facial features. Biallelic pathogenic variants of TMEM94 are associated with IDDCDF. Methods and Results: In a prenatal setting, where fetal abnormalities were detected using antenatal sonography, we used trio-exome sequencing (tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…At present we can only speculate, but the LXRactivating capacity of 22R-HC and 20R,22R-diHC and the expression of both LXRα and β during mammalian development makes it tempting to speculate that 20R-HC, 20R,22R-diHC and also 20S-HC by activating LXR, and in the case of 20S-HC by binding to Smo and Tmem97, are important for development of the embryo (Figure 9). In this regard, biallelic variants of Tmem97 were recently associated with fetal abnormalities (56). Little is known about the biological activities of trihydroxycholesterols and trihydroxycholestenoic acids and it is unknown whether 20R,22R,26-triHC, 3β,20R,22R-triHCA and 3β,20R,22R-triH-Δ 24 -CA are simply inactive intermediates on the road to bile acids or biologically active molecules themselves.…”
Section: Discussionmentioning
confidence: 99%
“…At present we can only speculate, but the LXRactivating capacity of 22R-HC and 20R,22R-diHC and the expression of both LXRα and β during mammalian development makes it tempting to speculate that 20R-HC, 20R,22R-diHC and also 20S-HC by activating LXR, and in the case of 20S-HC by binding to Smo and Tmem97, are important for development of the embryo (Figure 9). In this regard, biallelic variants of Tmem97 were recently associated with fetal abnormalities (56). Little is known about the biological activities of trihydroxycholesterols and trihydroxycholestenoic acids and it is unknown whether 20R,22R,26-triHC, 3β,20R,22R-triHCA and 3β,20R,22R-triH-Δ 24 -CA are simply inactive intermediates on the road to bile acids or biologically active molecules themselves.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Consanguinity increases the likelihood that a husband and wife may have a gene that originated from a common ancestor. Numerous studies have shown that children of such a marriage are more likely to be homozygous for a dangerous gene and subsequently have autosomal recessive genetic diseases [75][76][77] . Other researchers, however, examined seven (25%) children with consanguineous parents who had HD (P = 1.000) and found no evidence of a connection between the two.…”
Section: Prenatal Causesmentioning
confidence: 99%